1993
DOI: 10.1111/j.1570-7458.1993.tb01729.x
|View full text |Cite
|
Sign up to set email alerts
|

The inheritance of a wingless character in the 2spot ladybird (Adalia bipunctata)

Abstract: A viable wingless 2spot ladybird Adalia bipunctata (L.) was found in the wild. Breeding through four generations revealed that the wingless trait was controlled by a recessive allele which displays variable levels of expression. The wingless ladybird is discussed in relation to its potential as a biocontrol agent. One ladybird also occurred in this stock which is suggestive of a supergene controlling the colour polymorphism in this species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…Inheritance of winglessness was first reported by breeding lines from a wingless individual found at The Uithof, Utrecht in The Netherlands in 1990 (Marples et al, 1993). They found that winglessness is controlled by an allele with a major phenotypic effect that is recessive to the normal winged one.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inheritance of winglessness was first reported by breeding lines from a wingless individual found at The Uithof, Utrecht in The Netherlands in 1990 (Marples et al, 1993). They found that winglessness is controlled by an allele with a major phenotypic effect that is recessive to the normal winged one.…”
Section: Introductionmentioning
confidence: 99%
“…The wingless form of the two-spot ladybird beetle, which lacks elytra and hind wings, has been found occasionally in field populations (Majerus and Kearns, 1989;Marples et al, 1993). Inheritance of winglessness was first reported by breeding lines from a wingless individual found at The Uithof, Utrecht in The Netherlands in 1990 (Marples et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Hagen, 1962Kieckhefer and Olson, 1974Ignoffo et al, 1977Dreistadt and Flint, 1996Obrycki and Kring, 1998Dixon, 2000 Hippodamia convergens Guérin-Méneville 300 24 15 Kieckhefer and Olson, 1974 H. convergens Obrycki and Kring, 1998Dixon, 2000Obrycki et al, 2009 Harmonia axyridis Pallas Trouve et al, 1997Obata and Johki, 1990Ives et al, 1993Hodek and Honek, 1996Minoretti and Weisser, 2000Osawa, 2000Křivan, 2008Seagraves, 2009Frazer, 1988Hodek et al, 1993Ives et al, 1993 Elliott et al, 2000 Minoretti andWeisser, 2000 Hodek et al, 1993Hodek and Honek, 1996Hurst et al, 1996Osawa, 2000Evans, 2003Brown et al, 2011Tourniaire et al, 1999Ives, 1981van der Werf et al, 2000 3. Tamaki and Weeks, 1973Ignoffo et al, 1977Frazer, 1988Marples et al, 1993Ferran et al, 1996Ignoffo et al 1977 Table 1 20 36 Table 1 Seko and Miura, Mousseau and Dingle, 1991Roff, 1992Mousseau and Fox, 1998<...>…”
mentioning
confidence: 99%
“…Marples et al (1993) suggested that if ladybirds were poor flyers they would remain on a crop for longer and have potential in the long-term control of aphids. Flightless strains have been established from laboratory and field populations of the Coccinellids Harmonia axyridis (Pallas) (Ferran et al, 1998;Tourniaire et al, 2000;Seko et al, 2008), Adalia bipunctata (with a wingless morph) (L.) (Marples et al, 1993;Ueno et al, 2004;Lommen et al, 2005), and Rhyzobius litura (F.) (with a short-winged morph) (Hammond, 1985). Some of these strains are effective for augmentative biological control of aphids (Ferran et al, 1998;Weissenberger et al, 1999;Lommen et al, 2008;Seko et al, 2008).…”
Section: Introductionmentioning
confidence: 99%